Xbee Pro S1 Based Wireless Data Acquisition System for Landslide Monitoring - Rika Ratnasari; Rahadi Wirawan; Laili Mardiana; Jakrapong Kaewkhao (Journal of Science and Science Education, 2021)
Landslides are disasters that occur due to the shifting of land. To detect it, we need a system that can monitor it in real-time. Therefore, in this study, a wireless data acquisition system based on the Xbee Pro S1 module was built for monitoring landslides so that the community quickly responded in the event of a disaster. Testing the range of the module is very important to ensure that data communication between the transmitter and receiver can take place. The test carried out in this study was to take the plate distance data on the extensometer by adding a load and then detected using an ultrasonic sensor. The Xbee transmitter sends data to the Xbee receiver in real-time. From the test results, the maximum range of the Xbee Pro S1 module is 150m outdoors with an average delivery time of 15s from the transmitter to the receiver